Clonagem e expressão de protease mitogênica de Carica candamarcensis - Natassia Caroline Resende Correa (2009)
Cysteine proteinases are found in many organisms and play essential functions in parasites, mammals and plants. Carica candamarcensis, a member of the Caricaceae family, contains highly active cysteine proteinases in its latex. One of the proteins isolated from this specie was named CMS2MS2, it contains 214 aminoacids, exhibits proteolytic activity and shows mitogenic effect on mammal cells. The objective of this study was to produce recombinant CMS2MS2 to further study the biological activity and structure characterize this enzyme. To clone this gene a degenerate primer pair was derived from the recently elucidated N- and C-terminal sequence of CMS2MS2,. Amplicons of about 650 bp and 500 bp were obtained by PCR from the cDNA, generated by reverse transcription using total RNA from leaf. Initial cloning of the 650 bp fragment was done into plasmid pCR 2.1, which was transformed into Escherichia coli TOP10. Positive clones were confirmed by endonuclease digestion, specific PCR and sequencing. It was shown that F2 and E3 clones could be isoforms of cysteine-proteases in C. candamarcensis. The F2 clone was chosen and excised from pCR 2.1 with XhoI and HindIII enzymes for sub-cloning into pET28a(+)-TEV vector, between SalI e HindIII sites. The expression profile in BL21-DE3 bacteria induced with 0.5 mM IPTG showed a protein with approximately 30 kDa, as expected. The protein is only present in the insoluble fraction of the bacterial lysate. The mitogenic activity of the recombinant protein showed that the protein has proliferative effect on L929 fibroblasts at 0.4 e 1 nM concentrations, while in primary cultured osteoblasts it induces mitogenesis at 1 nM concentration which is within the pharmacological range exhibited by the non-recombinant enzyme.